Fostering Structural Change? China’s Divergence and Convergence with Africa’s Other Trade and Investment Partners - (:unkn) unknown (My University, 2016)
The paper analyses the divergence and convergence of the characteristics of China’s economic relationships with Africa – trade, investment and aid – with Africa’s ‘traditional’ partners, i.e. Western industrialised countries. It argues that these relationships may foster structural transformation of African economies. The latter have indeed exhibited spectacular growth rates since the early-2000s, which have partly been driven by China, via China’s demand for goods produced in sub-Saharan Africa and its contribution to high commodity prices. In addition, China’s relationships with sub-Saharan Africa are driven by investment, not only in African countries’ infrastructure, but also in industrial sectors, both being key determinants of structural transformation. The paper reveals the convergence of the trade relationships between China and sub-Saharan Africa with those of industrialised countries and sub-Saharan Africa, in particular similar ambivalent effects (the detrimental effects of commodity-based trade patterns and the positive effects of investment). However, in addition to differences regarding conditional aid, China’s specific modalities regarding trade and investment may make an original contribution to Sub-Saharan Africa’s structural transformation.
Keywords: African Research